Projeto de Vida no ensino médio: currículo oficial e currículo em ação em escolas do Programa Ensino Integral do estado de São Paulo - Mello, Sonia Regina Moraes de (Universidade Federal de São Carlos, 2024)
The investigation that gave rise to this dissertation was developed within the scope of the Study and Research Group on School Organization: Democracy, Human Rights and Manager Training – DEFORGES. The problem investigated is the following question: how do teachers perceive the implications teaching of the Life Project subject in the training of high school students in Comprehensive Education Program (PEI)? The general objective was to characterize these perceptions within the scope of this subject, in high school, in three PEI schools in the southwest of the São Paulo state. The specific objective was to investigate how teachers understood student improvement from the curricular perspective of the Life Project subject. The methodology used was education research qualitative exploratory, using document analysis, semi-structured interviews and classes observations as research instrument. The results obtained showed that teachers were not clear about the curriculum plan of the Life Project subject. Furthermore, teachers found it difficult to carry out school work and, sometimes, the teaching becomes unfeasible. In addition, education professionals pointed out the disconnection between the guidelines, the materials prescribed by the São Paulo State Department of Education (SEDUC-SP) and the real conditions for the development of this subject. The results also showed that the intentions of these guidelines and materials seem to be purposefully related to the qualification of labor for the job market in the current neoliberal context.
Life Project in high school: official curriculum and curriculum in action in schools of the Comprehensive Education Program from São Paulo state
Keywords: Projeto de vida; Currículo; Programa ensino integral; Life project; Curriculum; Comprehensive education program; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::CURRICULOS ESPECIFICOS PARA NIVEIS E TIPOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::TEORIA GERAL DE PLANEJAMENTO E DESENVOLVIMENTO CURRICULAR; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::ECONOMIA DA EDUCACAO